The Effectiveness of English Subtitle Videos on Vocabulary Mastery of Non-EFL Students at STIKES Jayapura Papua - Krishinta Mery Anggarwaty Kurniawan; Heni Purwati (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2023)
This study aims to investigate the impact of using English videos with and without subtitles on students' vocabulary mastery and to gauge their perceptions of both techniques. The study's population comprises 70 nursing program students at STIKES Jayapura. The study employs a quantitative experimental research design. The study's findings indicate a significant difference between students taught using English videos with subtitles and those taught without subtitles. Following the treatment, the experimental class's pre-test and post-test results showed a significant increase compared to the control group, with the experimental class's mean increasing from 6.22 to 23.07 compared to the control group. The t-test calculation result shows that the t-count of 2.279 is higher than the t-table of 1.999 at the degree of freedom (df) of 68. This result suggests that using subtitle videos is more effective in improving students' vocabulary mastery than videos without subtitles. Moreover, students respond more positively to subtitles in the videos played in the English classroom, making the class atmosphere more relaxing and enjoyable. Subtitles in the videos not only help students enhance their vocabulary but also provide entertainment through pictures and audio presented in the video. Additionally, teachers can choose various English videos relevant to students' needs and learning materials to make this strategy more effective in improving students' English skills and competence.